Tetra 4-(propargyloxy)phenoxy phthalocyanines: synthesis, spectroscopic, nonlinear optical and electrocatalytic properties - Mwanza, Daniel (Rhodes University, Faculty of Science, Department of Chemistry, 2017)
This study presents the synthesis, spectroscopic, photophysical and theoretical characterisation of metal-free (H2TPrOPhOPc), cobalt (CoTPrOPhOPc) and manganese (MnTPrOPhOPc) tetra 4-(4-propargyloxy) phenoxy phthalocyanines. Thermal analysis using thermogravimetric analysis (TGA) confirmed the excellent thermal stability of synthesized tetra 4-(4- propargyloxy) phenoxy phthalocyanines. The metal complexes, CoTPrOPhOPc and MnTPrOPhOPc, exhibited better thermal stability when compared to H2TPrOPhOPc. The residual percentage weight remaining was approximately 70% for CoTPrOPhOPc and MnTPrOPhOPc and 45% for H2TPrOPhOPc after 600Â°C, clearly confirming the stability of the metal complexes. The MTPrOPhOPcs (where M = H2, Co and Mn) complexes exhibited excellent nonlinear optical properties with strong reverse saturable absorption (RSA), especially when 560 nm excitation laser was used. Their nonlinear optical properties followed this trend: H2TPrOPhOPc > CoTPrOPhOPc > MnTPrOPhOPc. According to the trend observed, the H2TPrOPhOPc was an excellent nonlinear optical limiter when compared to the CoTPrOPhOPc and MnTPrOPhOPc. All the investigated complexes exhibited optical limiting properties comparable to the phthalocyanine complexes reported in the literature. The MTPrOPhOPc complexes were further studied for their electrocatalytic and electroanalytical properties towards the detection of hydrogen peroxide. For the electrocatalytic studies, the synthesized complexes were immobilized onto gold electrode surfaces pre-functionalized with phenylazide (Au-PAz) monolayer. Copper (I) catalyzed alkynyl-azide cycloaddition reaction was used to covalently immobilize the MTPrOPhOPcs onto the gold electrode surfaces to form Au-PAz-MTPrOPhOPc. The MTPrOPhOPcs modified gold surfaces (Au-PAz-MTPrOPhOPc) exhibited good reproducibility and stability in various electrolyte conditions. Electrochemical and surface characterisation of the functionalised gold electrode surfaces confirmed the presence of the MTPrOPhOPcs and their electroanalysis was excellent towards electrocatalytic reduction of H2O2, with the limit of detection (LoD) and limit of quantification (LoQ) in the ^M range. The electrocatalytic reduction peaks for H2O2 were observed at -0.37 V for Au-PAz-MnTPrOPhOPc and -0.31 V for Au-PAz-CoTPrOPhOPc when Ag

AgCl pseudo-reference electrode was used. The Au-PAz-MnTPrOPhOPc and Au- PAz-CoTPrOPhOPc gold electrode surfaces showed good sensitivity and reproducibility towards the electrocatalytic reduction of hydrogen peroxide in pH 7.4 phosphate buffer solution.
Keywords: Phthalocyanines; Nonlinear optics; Electrocatalysis; Spectrum analysis; Thermogravimetry; Phthalocyanines Spectra